Fenofibrate modified-release pellets with lag phase and high oral bioavailability - Li F; Zheng X; Bao YC; Chen T; Zeng J; Xu XL; Yan C; Feng LL (Dove Medical Press, 2018)
Fang Li,1,* Xin Zheng,2,* YongChu Bao,3 Ting Chen,3 Jia Zeng,1 XiaoLi Xu,4 Chao Yan,5 LingLin Feng1 1NHC Key Laboratory of Reproduction Regulation (Shanghai Institute of Planned Parenthood Research), Fudan University, and Shanghai Engineer and Technology Research Center of Reproductive Health Drug and Devices, Shanghai, China; 2Harro Hoefliger Shanghai Representative Office, Shanghai, China; 3Zhitong Laboratories Co., Ltd, Shanghai, China; 4Traditional Chinese Medicine Testing Department, Chongqing Institute for Food and Drug Control, Chongqing, China; 5Schoolof Pharmacy, Shanghai Jiao Tong University, Shanghai, China *These authors contributed equally to this work Purpose: Fenofibrate and statin combination therapy is highly recommended by the current clinical guidelines for treatment of mixed dyslipidemia. In this study, an innovative delayed-release preparation of fenofibrate was designed to reduce the risk of muscle toxicity, caused by simultaneous administration of this combination therapy, by altering the pharmacokinetic profile of fenofibrate, as well as to improve the oral bioavailability of the modified-release formulation.Methods: Micronized fenofibrate was used to prepare drug-loaded cores via a powder layering process before multiparticulate pellet coating. Different coating formulations (Eudragit® RS PO/E100, Eudragit® RS PO/RL PO, Eudragit® NE30D/HPMC, and EC/HPMC) were screened, and their in vitro release was compared with the commercial sustained-release pellets Lipilfen®. Two optimized formulations were evaluated in beagle dogs using two commercial preparations of fenofibrate (the immediate-release preparation Lipanthyl® and the sustained-release pellets Lipilfen®) as references.Results: The in vivo release of fenofibrate from R1 and R2 selected from in vitro tests exhibited a lag phase, and then rapid and complete drug release. The relative bioavailabilities of R1 and R2 were 100.4% and 201.1%, respectively, which were higher than that of Lipilfen® (67.2%).Conclusion: The modified fenofibrate pellets developed showed enhanced bioavailability and delayed-release properties. They have the potential to improve safety and compliance when co-administrated with statins. This is the first report of a delayed-release fenofibrate preparation. Keywords: fenofibrate, modified-release pellets, coated multiparticulate pellet, pharmacokinetics, in vivo studies